Kinetic for fermentation process of wort during beer production - Granada-Díaz, Héctor Andrés; Salamanca Grosso, Guillermo (Revista Colombiana de Investigaciones Agroindustriales, 2020)
In this work, kinetics of the fermentation process is analysed considering the reduction of sugars in the must, ethanol production, the generation of butanedione and ethyl acetate, through dynamic equations associated with the effect of temperature and its incidence on the Multi-objective optimization of the process. A contribution to the kinetic modelling system is presented with the inclusion of Arrhenius-type expressions on dynamic quantifications, which consolidate number of system parameters reduction. It is possible to describe the magnitude and extension of the process visualizing key concentrations for ethyl alcohol, ethyl acetate and diacetyl, as a function of initial substrate variables, considering the growth and inhibition rates. It was confirmed that the fermentable sugar contents govern the alcohol concentration at different temperatures and process times.